Preliminary study on biogas production from organic kitchen waste degradation / Wan Siti Atikah Wan Omar ...[et al.] - Wan Omar, Wan Siti Atikah; Jamil, Zadariana; Md Isa, Nurun Nadhirah; Abdullah, Nur Suraya; Wan Ismail, Wan Hanisah (2010)
Biogas is an important development in the pursuit of renewable energy and sustainable development in Malaysia. Biogas is obtained through anaerobic digestion of organic waste (i.e. agricultural waste, food waste). Tons of food waste are generated from high concentration point sources e.g. restaurants, cafes, markets et cetera and finally dumped at landfills. This paper presents the preliminary study of anaerobic digestion of local kitchen waste for biogas production. In this study a modified 22L High Density Polyethylene (HDPE) reactor was designed for a batch anaerobic system. The kitchen waste was obtained from two cafeterias, grinded and fermented anaerobically for 11 days. The three layers (top, middle and bottom) of the food waste (substrate) in the HDPE reactor were analyzed daily. Metabolic products produced from the anaerobic digestion were acetic acid, propionic acid, and butyric acid Throughout the fermentation process, the pH range was from 3.8 to 2.8. The Chemical Oxygen Demand (COD) range during the digestion process was 45-226 mg/L. The resident microorganisms in the reactor were found as rod-shape Gram (+) and Gram (-), cocci Gram (+) and yeast. However, the volume of biogas produced was very low at 133 µmol L-1 d1 . The low pH range in the reactor was hypothesized to be the reason for the low production of biogas.